Reasons for the low achievement in mathematics among students of the first three grades of the basic education stage from the viewpoint of teachers and educational supervisors in Benghazi city - Libya - Mohamed, Fatma Naser Ali; Bukhatwa, Bothaina Fadil; Alagelee, Haajer Ayad Mohamed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to to investigate the reasons for the low achievement in mathematics among the students of the first three grades of the basic education stage as perceived by teachers and educational supervisors in Benghazi. To achieve the objectives of the study, the researchers employed the descriptive approach, and designed a questionnaire to collect data. The sample comprised (88) mathematices teachers and (14) educational supervisors working in the basic education stage in Benghazi. The study findings indicated that the teachers and educational supervisors agreed that the reasons for the low achievement in mathematics were related to (the student and their family, the teacher, and the curriculum). The teachers' responses indicated a high level of agreement on these factors, while the educational supervisors' responses showed a very high level of agreement on the teacher and curriculum factors and a high level of agreement on the student and family factor. Moreover, the study revealed significant differences between the teachers' and educational supervisors' responses to the reasons for low achievement in mathematics. The educational supervisors' responses were more significant, indicating a better understanding of the problem. Based on these results, the researchers suggested a few recommendations, including abolishing the deportation system, reducing teachers' workload, developing plans and programs to address learning difficulties, and offering more training courses for teachers.
Keywords: Low achievement; first three grades students; mathematics; school teachers; educational supervisors